Family Financial Management Education as an Effort to Reduce Dependence on “Bank Tongol” in Sadran Puton Hamlet - Al Mu’ta’zim, M. Tsany; Safira, Seena; Sofiyani, Anisa; Safira, Vina Aulia; Atmarini, Resti; Susiatmi, Sandi Ari; Kholidah, Nur (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
The dependence of rural communities on informal financial institutions, such as